2010
DOI: 10.1007/s00296-010-1431-4
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II, MICA and PRL gene polymorphisms: the common contribution to the systemic lupus erythematosus development in Czech population

Abstract: ObjectiveThe genetic components contribute to the Systemic lupus erythematosus development. This study for the first time determined the distribution of the polymorphisms and linkage disequilibrium in HLA class II, MICA and PRL gene among patients suffering from SLE and healthy Czech individuals. Patients and Methods DNA ConclusionHLA class II-MICA combinations may increase/decrease a risk for SLE development.Multiple studies focusing on the ethnical differences as well as genetic-epigenetic relationships are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
2
14
1
Order By: Relevance
“…In contrast to the authors' findings on T cells, we could not detect any influence of NGF on NK cell proliferation, and NGF also did not support the survival of NK cells (2). In addition, NGF did not modulate cytotoxicity and cytokine production by NK cells, although we only tested for interferon-␥ and IL-10.…”
Section: To the Editorcontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the authors' findings on T cells, we could not detect any influence of NGF on NK cell proliferation, and NGF also did not support the survival of NK cells (2). In addition, NGF did not modulate cytotoxicity and cytokine production by NK cells, although we only tested for interferon-␥ and IL-10.…”
Section: To the Editorcontrasting
confidence: 99%
“…Furthermore, we have recently shown that ϳ20% of freshly isolated NK cells from mouse spleens express TrkA, but that this percentage increases to 100% after a few days of culture in the presence of interleukin-2 (IL-2) (2). Similar to T cells (1), the subset of NK cells expressing the neurotrophin receptor p75 NTR is extremely low (2).…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…T cells play a central role in immune protection which recruits neutrophils, eosinophils, and basophils to sites of infection and inflammation, to help B cells make antibodies, to induce macrophages to develop enhanced microbicidal activity, and through their production of cytokines and chemokines, to orchestrate the full panoply of immune responses [7]. Thereby, lot of studies demonstrated that there is close relationship between the HLA gene polymorphisms and infection disease, cancer, inflammatory, and autoimmune disease [8][9][10][11][12][13]. In addition, growing studies found that the HLA Class II gene, especially HLA-DRB1 gene polymorphisms, might significantly influence of TB risk [14][15][16], but the results have been inconclusive.…”
Section: Introductionmentioning
confidence: 97%